In Vitro and in Vivo Study of the Effect of Osteogenic Pulsed Electromagnetic Fields on Breast and Lung Cancer Cells - Mike Y. Chen; Jing Li; Nianli Zhang; Erik I. Waldorff; James T. Ryaby; Philip Fedor; Yongsheng Jia; Yujun Wang (SAGE Journals, 2022)
Introduction: Although there have been significant advances in research and treatments over the past decades, cancer remains a leading cause of morbidity and mortality, mostly due to resistance to standard therapies. Pulsed electromagnetic field (PEMF), a newly emerged therapeutic strategy, has been highly regarded as less invasive and almost safe to patients, is now a clinically accepted form to treat diseases including cancer. Breast and lung cancer are the most prevalent forms of human cancers, yet reported investigations on exploring regimes including PEMF are limited. Methods: Intended to examine the anti-tumor effects of a clinically accepted osteogenic PEMF and the possibility of including PEMF in breast and lung cancer treatments, we studied the effects of 2 PEMF signals (PMF1 and PMF2) on breast and lung cancer cell growth and proliferation, as well as the possible underline mechanisms in vitro and in vivo. Results: We found that both signals caused modest but significant growth inhibition (∼5%) in MCF-7 and A549 cancer cells. Interestingly, mice xenograft tumors with A549 cells treated by PEMF were smaller in sizes than controls. However, for mice with MCF-7 tumor implants, treatment with PMF1 resulted in a slight increase (2.8%) in mean tumor size, while PMF2 treated tumors showed a 9% reduction in average size. Furthermore, PEMF increased caspase 3/7 expression levels and percentage of annexin stained cells, indicating the induction of apoptosis. It also increased G0 by 8.5%, caused changes in the expression of genes associated with cell growth suppression, DNA damage, cell cycle arrest, and apoptosis. When cancer cells or xenograft tumors treated with combined PEMF and chemotherapy drugs, PEMF showed growth inhibition effect independent of cisplatin in A549 cells, but with added effect by pemetrexed for the inhibition of MCF-7 growth. Conclusion: Together, our data suggested that clinically used osteogenic PEMF signals moderately suppressed cancer cell growth and proliferation both in vitro and in vivo.
Keywords: Oncology and Carcinogenesis not elsewhere classified; Radiology and Organ Imaging; Biochemistry